1990
DOI: 10.1161/01.cir.81.6.1762
|View full text |Cite
|
Sign up to set email alerts
|

Indirect evidence for release of endothelium-derived relaxing factor in human forearm circulation in vivo. Blunted response in essential hypertension.

Abstract: In isolated blood vessels, acetylcholine releases endothelium-derived relaxing factor (EDRF). In vivo, the vasodilator action of acetylcholine may be mediated by EDRF, but prostacyclin or prejunctional inhibition of adrenergic neurotransmission may also be involved. Therefore, we investigated whether acetylcholine releases EDRF in humans in vivo and, if so, whether the response altered in essential hypertension. Acetylcholine was infused into the brachial artery, and forearm blood flow measured by venous occlu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
322
5
20

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 704 publications
(362 citation statements)
references
References 35 publications
15
322
5
20
Order By: Relevance
“…In contrast, pharmacological agents (e.g., acetylcholine) are administered by intra-arterial infusion in a dose-dependent manner to test vasoreactivity of the brachial artery. The other forearm serves as internal control due to minimal systemic effect of the infusion [42]. Generally, FMD and plethysmography are better suited for serial or longitudinal studies than between-group testing due to interindividual variability [43].…”
Section: How Can We Measure Endothelial Function?mentioning
confidence: 99%
“…In contrast, pharmacological agents (e.g., acetylcholine) are administered by intra-arterial infusion in a dose-dependent manner to test vasoreactivity of the brachial artery. The other forearm serves as internal control due to minimal systemic effect of the infusion [42]. Generally, FMD and plethysmography are better suited for serial or longitudinal studies than between-group testing due to interindividual variability [43].…”
Section: How Can We Measure Endothelial Function?mentioning
confidence: 99%
“…Recently, several investigators, including us, have evaluated the effects of intra-arterial infusion of NO agonists, such as acetylcholine, methacholine and bradykinin, and intra-arterial infusion of NO antagonists on forearm blood flow using a mercury-filled Silastic strain-gauge plethysmography and the effects on coronary blood flow using a Doppler flow guide wire. [9][10][11]17,26,27,35 The responses to intraarterial infusion of vasoactive agents should be most suitable for assessing endothelial function, because the use of agonists to stimulate NO release and the use of antagonists of NO allow us to draw more specific conclusions concerning the role of basal and stimulated NO release. However, the invasive methods are time consuming and are a burden for patients.…”
Section: Endothelial Functionmentioning
confidence: 99%
“…37 In hypertensive patients also, endothelium-dependent vascular relaxation in coronary, forearm and renal arteries was found to be impaired, and endothelial dysfunction, which is involved in the development of atherosclerosis, was found to increase the risk of cardiovascular and cerebrovascular diseases. [9][10][11][12][13][14][15]27,35 As Panza et al 9 reported for the first time in 1990 that the dose-response curve obtained by acetylcholine in patients with hypertension was smaller than the curve in normal controls and that the dose-response curves obtained by sodium nitropreside were similar in the two groups, suggesting that endothelial function, but not smooth muscle function, is selectively impaired in patients with hypertension, a large number of studies have shown that hypertension is associated with endothelial dysfunction.…”
Section: Endothelial Dysfunction and Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 It has previously been shown that endothelium-dependent vasodilatation is impaired in hypertensive subjects. 16,17 It therefore seems likely that a defect in the NO-system plays a role in the blunted effect of insulin on TPRI seen in this sample of hypertensive subjects.…”
Section: Figurementioning
confidence: 84%